Association Between Chinese Herbal Medicine Therapy and the Risk of Chronic Kidney Disease in Gout Patients - Xiao, Yan-Zhuan; Ye, Zhi-Zhong; Liang, Yuan-Tong; Chen, Xin-Peng; Wang, Yu-Hsun; Xu, Qiang; Wei, James Cheng-Chung (Frontiers in Pharmacology, 2021)
Background: Chinese herbal medicine (CHM) has been nationally and globally used in treating gout for over a millennium. The potential relationship between the incidence of chronic kidney disease (CKD) in gout patients and CHM therapy is unclear. Thus, this study aimed to provide some evidence regarding the relationship between CHM therapy and the occurrence of CKD in gout patients. Methods: We used data from the National Health Insurance Research Database (NHIRD) in Taiwan. In this population-based nested case-control study, all participants were identified by International Classification of Diseases, Ninth Revision (ICD-9). Conditional logistic regression was used to calculate the odds ratio (OR) of the risk of CKD in gout patients treated with CHM therapy. Results: Data on 1718 gout patients with CKD and 1:1 matched 1718 gout patients without CKD were collected for analysis. The results showed that CHM therapy in gout patients did not increase the risk of developing CKD (adjusted OR = 1.01; 95% confidence interval [CI]: 0.86–1.18; p > 0.05). Moreover, CHM therapy in gout patients for >365 days did not increase the incidence of CKD (adjusted OR = 1.30; 95% CI: 0.90–1.88; p = 0.162). Conclusions: Traditional CHM therapy does not increase the incidence of CKD in gout patients.